Concentration of total dissolvable and total iron, manganese, cobalt and nickel in the water column at 5 sites along a water depth transect in the Gulf of Mexico (Louisiana continental shelf) - Wytze K Lenstra (PANGAEA, 2022)
The concentration of Fe in water column samples was determined by flow injection chemiluminescence with preconcentration detection. Total dissolvable Fe concentrations were determined 3 months after sample collection. All samples per station were analyzed in triplicate in the same run. The blank of acidified ultrapure water (pH = 1.8) was 32 ± 39 pmol L-1 (n = 194). The average limit of detection (LOD), calculated as the standard deviation of the analysis of oligotrophic seawater with known trace metal concentrations, multiplied by 3, was 86 ± 120 pmol L-1 (n = 19). The concentrations of Co, Mn, and Ni were determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS; Nexion ICP-MS (Perkin Elmer)) after pre-concentration with an SC-DX SeaFAST S2 (Elemental Scientific). Total dissolvable Co, Mn, and Ni were determined 7 months after sample collection. The LOD values for Co, Mn, and Ni were 0.027 ± 0.004, 0.11 ± 0.024, and 0.99 ± 0.12 nmol L-1 (n=5), respectively, and the values of the oligotrophic seawater were 0.77 ± 0.9, 0.9 ± 0.5, and 4.41 ± 0.52 nmol L-1 (n=40), respectively.